Prevalence of Neck Pain and its Related Factors in Nurses Working in Intensive Care Units of Hospitals in Northern Iran - Ali Ashraf; Zoheir Rehanian; Kamran Ezzati; Roxana Mahdavi; Habib Eslami Kenarsari; Sedigheh Samimian (Journal of Holistic Nursing and Midwifery)
Introduction: Nursing is a job with high physical activity; therefore nursed are at high risk of work-related musculoskeletal disorders, including neck pain. Objective: This study aims to investigate the prevalence and risk factors of neck pain in nurses working in intensive care units (ICUs) of teaching hospitals in Rasht, north of Iran. Materials and Methods: In this cross-sectional study, 120 nurses working in the ICUs of seven educational therapeutic hospitals in Rasht in 2019 participated. Required data were collected using a two-part questionnaire. The first part surveyed sociodemographic information. The second part was the Persian version of the neck disability index. For statistical analysis, chi-square test, Fisher’s test, and logistic regression analyses were used. Results: The mean age of nurses was 35.7±5.8 years, and 97.5% of them were female. Their mean work experience was 11.1±5.6 years. The overall prevalence of neck pain was 82.5% (n=99). The frequency of neck pain among nurses with more than 15 years of work experience (P=0.019), age 30-39 years (P=0.031) and no sports activity (P=0.031) was more. The risk of neck pain in nurses who had a history of exercise was 3.277 times higher (95% CI; 1.030%, 10.43%, P=0.045) and in married nurses was 2.92 (95% CI; 0.920%, 9.274%, P=0.069) that was borderline significant. Conclusion: There is a high prevalence of neck pain among nurses working in the ICUs of educational therapeutic hospitals in Rasht. Hence, it is necessary for hospital managers to take the necessary measures to reduce these complications in order to protect the health of nurses and improve the quality of patient care.